2012
DOI: 10.1007/s10725-012-9701-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term copper (Cu2+) exposure impacts on auxin, nitric oxide (NO) metabolism and morphology of Arabidopsis thaliana L.

Abstract: Plants are able to dynamically adapt to their environment by reprogramming of their growth and development. Copper (Cu 2?) excess modifies shoot and root architecture of plants by a lesser known mechanism, therefore the involvement of a major hormone component (auxin) and a signal molecule (nitric oxide) in Cu 2?induced morphological responses were studied in Arabidopsis using microscopic methods. Auxin-inducible gene expression was visualized in DR5::GUS Arabidopsis and nitric oxide (NO) levels were detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Moreover, Katekar and Geissler (1982), reported that under chloride presence, pea plants form chlorinated indole acetic acid that has higher affinity than IAA for auxin receptors; thus, reducing the IAA activity in plants. In addition, Kolbert et al (2012), reported that in Arabidopsis thaliana, Cu stress decreased the auxin-dependent gene expression, resulting in a reduction of root growth. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Katekar and Geissler (1982), reported that under chloride presence, pea plants form chlorinated indole acetic acid that has higher affinity than IAA for auxin receptors; thus, reducing the IAA activity in plants. In addition, Kolbert et al (2012), reported that in Arabidopsis thaliana, Cu stress decreased the auxin-dependent gene expression, resulting in a reduction of root growth. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cu at high concentrations affects the auxin content in the cotyledons and apices of primary roots of Arabidopsis [29]. Cu led decline in the auxins levels was reported by Kolbert et al [30] in Arabidopsis thaliana L. plants, which was responsible for the decrease in the growth of plants. IAA application enhanced the total FW of Musa sp.…”
Section: -Epibrassinolide Mediated Regulation Of Endogenous Contentmentioning
confidence: 70%
“…Interestingly, there was no difference between wild-type (WT) and a NO-overproducing mutant A. thaliana seedlings in response to exposure to Cu 2+ in excess (Peto et al 2011), suggesting a very minor role, if any, for NO being an endogenous signal in the morphological response to heavy metal stress. However, this interpretation might be complicated by the auxin homeostasis in the same tissue under the same stress (Peto et al 2011;Kolbert et al 2012).…”
Section: Root and Stem Growthmentioning
confidence: 99%
“…It would also seem that NO might play a minor role in the morphological response of cotyledons under abiotic stress. However, other parallel experiments studying auxin metabolism and transport in the wild-type, NO-overproducing, and NO-deficient A. thaliana seedlings in response to Cu 2+ treatments revealed a more complex network of antagonistic relationships between NO levels and auxin homeostasis (Peto et al 2011;Kolbert et al 2012). This has added implications to the conceptual framework that there are cross talks among ROS, auxin, and ethylene, which have already been considered as the important signals in the SIMRs (Potters et al 2009).…”
Section: Morphological Response Of Cotyledons Under Abiotic Stressmentioning
confidence: 99%